2014
DOI: 10.1098/rstb.2013.0465
|View full text |Cite
|
Sign up to set email alerts
|

How do cilia organize signalling cascades?

Abstract: Cilia and flagella are closely related centriole-nucleated protrusions of the cell with roles in motility and signal transduction. Two of the best-studied signalling pathways organized by cilia are the transduction cascade for the morphogen Hedgehog in vertebrates and the mating pathway that initiates gamete fusion in the unicellular green alga Chlamydomonas reinhardtii . What is the role of cilia in these signalling transduction cascades? In both Hedgehog and mating pathways, all signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
106
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(118 citation statements)
references
References 87 publications
4
106
1
Order By: Relevance
“…This was an unexpected localization for polycystic disease gene products since most fibrocystic diseases of the kidney and liver, including ADPKD, are associated with proteins that function in primary cilia (14). Primary cilia are minute solitary membraneenclosed micro tubule-based projections that serve as organelles integrating cellular sensory signals on the apical surface of many cell types, including bile duct and kidney tubule epithelial cells (15)(16)(17). Mutations in another noncilial protein, LDL receptorrelated protein 5 (LRP5), a coreceptor in canonical Wnt signaling, have also been implicated as causing PCLD (18).…”
Section: Introductionmentioning
confidence: 99%
“…This was an unexpected localization for polycystic disease gene products since most fibrocystic diseases of the kidney and liver, including ADPKD, are associated with proteins that function in primary cilia (14). Primary cilia are minute solitary membraneenclosed micro tubule-based projections that serve as organelles integrating cellular sensory signals on the apical surface of many cell types, including bile duct and kidney tubule epithelial cells (15)(16)(17). Mutations in another noncilial protein, LDL receptorrelated protein 5 (LRP5), a coreceptor in canonical Wnt signaling, have also been implicated as causing PCLD (18).…”
Section: Introductionmentioning
confidence: 99%
“…Hh signal transduction in mammals uses the primary cilium (Eggenschwiler and Anderson 2007;Wong and Reiter 2008;Berbari et al 2009;DeRouen and Oro 2009;Goetz and Anderson 2010;Bay and Caspary 2012;Drummond 2012;Oh and Katsanis 2012;Kim and Dynlacht 2013;Nozawa et al 2013;Mukhopadhyay and Rohatgi 2014;Nachury 2014), an evolutionarily conserved microtubule-based organelle analogous to the flagella found in single-celled eukaryotes such as Chlamydomonas reinhardtii (green algae). All core components of vertebrate Hh signaling localize to the primary cilium in a dynamic manner (Corbit et al 2005;Haycraft et al 2005;Rohatgi et al 2007;Chen et al 2009;Endoh-Yamagami et al 2009;Kim et al 2009;Liem et al 2009).…”
mentioning
confidence: 99%
“…Thus, the primary cilium is a sensing organelle functionally separated from the cytoplasm by the ciliary base, which controls the selective entry of ciliary proteins (Wei et al, 2015). A peculiar characteristic of primary cilia is the lack of actin cortex underlying the primary cilium membrane As discussed in the text (see also Nachury, 2014), a special role in the cell sentience can be played by the primary cilium in view of at least four conditions favoring their appropriate cross-talks among signaling molecules: 1. selection of the proteins reaching the cilium thanks a filtering apparatus at the cilium basis; 2. colocation of special signaling molecules in suitable cilium membrane compartments; 3. increased concentrations of signaling molecules in the cilium; 4. specific physicochemical intracilium microenvironment. Left panel: schematic representation of a primary cilium and its main structural peculiarities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that LRs can concentrate ion channels (Martens et al, 2004) and heterotrimeric G proteins and GPCRs (Allen et al, 2007). Obviously, the co-localization of pathway components permits the efficient transmission of signals between adjacent molecules while avoiding inappropriate cross-talk with other pathways in the cells (Agnati et al, 2007a;Negro et al, 2008). Furthermore, owing to partitioning into LRs, even a small increase in the local concentration of signaling molecules can cause a dramatic amplification of signaling cascades (Simons and Toomre, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation